The mechanism by which piR-000699 targets SLC39A14 regulates ferroptosis in aging myocardial <?A3B2 pi6?>ischemia/reperfusion injury - Chi Hongyang; Chai Yue’e; Ma Lingju; Wang Yichen; Wu Qianqian; Wang Lexin; Zhai Junjie; Ma Fufun; Tian Yancheng; Qi Ning; Peng Jianhong; Fu Youjuan; et al. (Acta Biochimica et Biophysica Sinica, 2024)
Myocardial ischemia/reperfusion (I/R) injury is a classic type of cardiovascular disease characterized by injury to cardiomyocytes leading to different types of cell death. The degree of irreversible myocardial damage is closely related to age, and ferroptosis is involved in cardiomyocyte damage. However, the mechanisms underlying ferroptosis regulation in aging myocardial I/R injury are still unclear. The present study aims to explore the underlying mechanism of piRNA regulation in ferroptosis. Using left anterior descending coronary artery ligation in an aging rat model and a D-galactose-induced rat cardiomyocyte line (H9C2) to construct an aging cardiomyocyte model, we investigate whether ferroptosis occurs after reperfusion injury in vitro and in vivo. This study focuses on the upregulation of piR-000699 after hypoxia/reoxygenation treatment in aging cardiomyocytes by observing hypoxia/reoxygenation (H/R) injury indicators and ferroptosis-related indicators and clarifying the role of piR-000699 in H/R injury caused by ferroptosis in aging cardiomyocytes. Bioinformatics analysis reveals that SLC39A14 is a gene that binds to piR-000699. Our data show that ferroptosis plays an important role in I/R injury both in vivo and in vitro. Furthermore, the results show the potential role of piR-000699 in regulating SLC39A14 in ferroptosis in aging cardiomyocytes under hypoxia/reoxygenation conditions. Together, our results reveal that the mechanism by which piR-000699 binds to SLC39A14 regulates ferroptosis in aging myocardial I/R injury. <?Pub Caret 24?>